EFEK EMOSI POSITIF SEBAGAI PEMBENTUK NIAT ADOPSI SISTEM INFORMASI LAYANAN PASIEN - Dewi, Tri Angga; Setyawan, Didik; Noor, Finisha Mahaesti (Jurnal Bisnis dan Kewirausahaan, 2018)
The purpose of this study is to examine the effect of perceptions and perceptions on the intention of adopting this system of information, with positive emotions as moderators. This study is important to examine the use of information systems in health workers by providing positive emotional effects. This research uses survey method through questionnaire. The object ofresearch is health workers who use the information system in PKU Muhammadiyah hospitals Surakarta with as many as 100 respondents ever used information system. Sample taking in this research using purposive sampling method. Analyzer used in this research is doubled linear regression and regresi moderasi. The results showed H1 and H2 supported except H3 and H4 were not supported. These results give meaning perceived usefulness and perceived ease to use affect adopt intention to adoption information systems, but not for positive emotions that have not affect betwent peceuved usefalnees and percejued ease of use to intention to adoption information systems.